UTILIZATION OF EGGSHELLS INTO CALCIUM POWDER FOR PLANTS WITH VINEGAR ADDITION IN GAMPONG LAMPISANG, PEUKAN BADA SUB-DISTRICT ACEH BESAR DISTRICT: PEMANFAATAN CANGKANG TELUR MENJADI BUBUK CALSIUMUNTUK TANAMAN DENGAN PENAMBAHAN CUKA DI GAMPONGLAMPISANG KECAMATAN PEUKAN BADAKABUPATEN ACEH BESAR - Abdullah, Umar Husein; Sri Agustina; Yusran Akbar; Elvi Zahara; Ika Rezvani Aprita; Hardiansyah A (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2024)
This Community Service (CS) activity aims to provide information to the community about the use of eggshells as a source of calcium fertilizer with the addition of vinegar in Gampong Lampisang, Peukan Bada Sub-District, Aceh Besar District. The method of CS activities is that lecturers and students conduct a Gampong location survey which aims to find out the potential and situation in the Gampong, then plan what things will need to be presented and demonstrated to the community. Then the second stage, giving a direct explanation to the community about the Utilization of Egg Shells into Calcium Powder for Plants with the Addition of Vinegar. CS activities carried out in Gampong Lampisang, Peukan Bada District, Aceh Besar District have been carried out very well and smoothly thanks to the assistance of several parties, namely the LPPM Politeknik Indonesia Venezuela, the support of village officials and the people of Gampong Lampisang. The community gained more knowledge about how to utilize the remaining products or eggshell waste into organic fertilizers that are useful for plants and reduce waste in Lampisang Village